EXPLORING THE DARK HORIZON : ARTIFICIAL INTELLIGENCE (AI) AS CYBERTERRORISM TOOLS - Krisnayanto, Krisnayanto; Suryadi, Suryadi (UI Scholars Hub, 2025)
This Journal utilizes a thorough literature review approach to explore the evolving relationship between artificial intelligence (AI) and its potential use as a tool for terrorism. With the rapid advancement of AI technologies, there is a growing concern about their possible misuse by terrorist groups. This study extensively examines existing research, policy documents, and expert opinions and investigates the complex connections between AI and terrorism. The literature review delves into historical examples, current case studies, and emerging trends to clarify the various ways in which AI could be employed for harmful purposes by terrorist organizations. By analyzing recruitment strategies, communication methods, propaganda dissemination, and attack planning, the study offers a detailed understanding of the potential risks associated with the intersection of AI and terrorism. Ethical and legal considerations are thoroughly examined, addressing issues of accountability and the necessity for regulatory frameworks to guide the ethical use of AI technologies in the context of terrorism. In response to the identified risks